A Dendrite‐Free Lithium‐Metal Anode Enabled by Designed Ultrathin MgF2 Nanosheets Encapsulated Inside Nitrogen‐Doped Graphene‐Like Hollow Nanospheres. Issue 24 (15th May 2022) - Li, Shang‐Qi; Zhang, Ling; Liu, Ting‐Ting; Zhang, Yao‐Wen; Guo, Chaofei; Wang, Yong; Du, Fei‐Hu
Abstract: Uncontrolled lithium dendrite growth and dramatic volume change during cycling have long been severely impeding the practical applications of Li metal as the ultimate anode. In this work, ultrathin MgF2 nanosheets encapsulated inside nitrogen‐doped graphene‐like hollow nanospheres (MgF2 NSs@NGHSs) are ingeniously fabricated to address these problems by a perfect combination of atomic layer deposition and chemical vapor deposition. The uniform and continuous Li–Mg solid‐solution inner layer formed by the MgF2 nanosheets can reduce the nucleation overpotential and induce selective deposition of Li into the cavities of the NGHSs. Furthermore, the Li deposition behavior and mechanism of the hybrid host are comprehensively explored by in situ optical microscopy at the macroscopic level, in situ transmission electron microscopy at the microscopic level, and theoretical calculations at the atomic level, respectively. Benefiting from a synergistic modulation strategy of nanosheet seed‐induced nucleation and Li‐confined growth, the designed composite demonstrates an endurance of 590 cycles for asymmetric cells and a lifespan over 1330 h for corresponding symmetric cells. When applied in LiFePO4 full cells, it provides a reversible capacity of 90.6 mAh g −1 after 1000 cycles at 1 C. Abstract : Ultrathin MgF2 nanosheets encapsulated inside N‐doped graphene‐like hollow nanospheres are prepared by the perfect combination of atomic layer deposition and chemical vapor deposition. In situ optical microscopy, in situ transmission electron microscopy, and theoretical calculations are used to investigate the deposition behavior and mechanism in detail. The Li‐metal batteries based on the designed composite anode demonstrate superior electrochemical performance.